Il padre Perotus. Su un errore di Vico - Pica Ciamarra, Leonardo (Laboratorio dell'ISPF, 2011)
[Father Perotus. About a mistake by Vico]. This paper proposes the recognition of a not yet identified person cited by G. Vico in his "De nostri temporis studiorum ratione" (1709): the father Perotus, who reportedly made an abortive attempt to build an ideal ship according to the rules of analytical geometry. Vico's "Perotus" (or Peroto, Perot, Perotti, as it has been variously translated) is identified as the French jesuit Paul Hoste, mathematician in Toulon at the end of the 17th Century.